Assessment of Tidal and Wave Energy Resource Potential in Malaysia with Sea Level Rise Effects - Zahara Yaakop; Hee-Min Teh; Vengatesan Venugopal; Zhe Ma (Journal of Marine Science and Engineering)
Ocean energy, e.g., waves, tidal current, and thermal and salinity gradient, can be used to produce electricity. These marine-based renewable energy technologies are at relatively early stages of development and potentially deployed at various sea conditions. In the past, numerous studies were undertaken to explore the feasibility of harvesting of the marine energy in Malaysia; however, those studies were limited to a specific location (i.e., the east coast of Peninsular Malaysia and East Malaysia) and the consideration of sea level rise effect was not studied. This study assessed the potential of tidal and wave energy resources in Malaysia’s waters with the effect of projected sea level rise and was undertaken through numerical modeling using MIKE 21 software. The research outcomes were tidal and wave energy contours for Malaysia’s waters with an inclusion of the sea level rise projection for 2060 and 2100, as well as a potential site determined for tidal and wave energy harvesting. The simulation results highlight the significant potential of tidal and wave energy in specific locations around Malaysia and its coastal regions, as well as in the South China Sea’s offshore regions. By incorporating sea level rise projections into tidal and wave simulations, we revealed a notable increase in tidal and wave power.